NEW APPROACH TO OIL PALM WOOD UTILIZATION FOR WOODWORKING PRODUCTION Part 1: Basic Properties - Balfas, Jamal (Indonesian Journal of Forestry Research, 2006)
An explosive development in oil palm plantations in the country has produced a consequence in the generation of  plantation wastes. The  disposal of these wastes  has created  an  enormous environmental problem that some practical solution to their economic utilization has to  be sought.  A series of experiments have been accomplished to observe the possibility of converting the oil palm stem into valuable woodworking products. The  first stage of  this effort was determining basic characteristics of oil palm wood.  Results in general showed that the wood has a great characteristic variation across and along the stem, which may develop problems in its utilization. Characteristics of this wood also vary according to species variety.  Quality degradations of oil palm wood were mostly happened during drying process; hence, modifications to upgrade quality should be undertaken before or within the drying process.